BIOLOGICAL CHARACTERISTICS OF APHIS POMI AND APHIS PUNICAE (BASED ON THE EXAMPLE OF SIRDARYA REGION) (Scientific journal of the Fergana State University, 2024)
This article studies in detail the biology of the aphids Aphis pomi and Aphis punicae, which are considered hardy in conditions of high population density, wide distribution area and damage to seed trees and shrubs in the Sirdarya region.